1976
DOI: 10.1128/aac.10.2.196
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effects of Low Concentrations of Penicillin and Sulfadiazine on Streptococcus mutans

Abstract: Investigations were conducted to determine the in vitro effects of low levels of penicillin and sulfadiazine on the growth, plaque formation, and agglutination ofStreptococcus mutans and on the synthesis and activity of enzymes synthesizing extracellular polymers. The concentrations tested were equivalent to those expected in the saliva of subjects receiving oral therapy with the agents. Penicillin at 0.5 ng/ml and sulfadiazine at 1 ug/ml substantially inhibited in vitro plaque formation. At these concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1976
1976
1980
1980

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The result with S. mutans was particularly surprising since an earlier study (26), using an in vitro quantitative assessment of S. mutans growth, had shown that low levels of sulfadiazine (1 to 10 jig/ml) inhibited growth, even though the organisms were resistant to the agent as judged by usual qualitative susceptibility testing procedures (3,20,21). It would seem that, if such an inhibition occurs in vivo, it was not of sufflcient magnitude to significantly alter the proportions of that organism in plaque.…”
Section: Resultsmentioning
confidence: 81%
“…The result with S. mutans was particularly surprising since an earlier study (26), using an in vitro quantitative assessment of S. mutans growth, had shown that low levels of sulfadiazine (1 to 10 jig/ml) inhibited growth, even though the organisms were resistant to the agent as judged by usual qualitative susceptibility testing procedures (3,20,21). It would seem that, if such an inhibition occurs in vivo, it was not of sufflcient magnitude to significantly alter the proportions of that organism in plaque.…”
Section: Resultsmentioning
confidence: 81%
“…Furthermore, young human patients (6 to 19 years old) who had received longterm administration of penicillin and/or tetracycline for treatment of chronic infectious diseases developed about two-thirds fewer caries than did control subjects (242). This observation could be explained by the recent finding that the presence of the very low concentrations of both penicillin G and sulfadiazine markedly inhibits in vitro plaque formation by S. mutans (607).…”
Section: Suppression Of S Mutans By Antimicrobialmentioning
confidence: 99%